2017
DOI: 10.1002/ange.201704322
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Reversible Formation of Iron(III)–Oxo–Cerium(IV) Adducts from Nonheme Oxoiron(IV) Complexes and Cerium(III)

Abstract: Ceric ammonium nitrate (CAN) or Ce IV (NH 4 ) 2 -(NO 3 ) 6 is often used in artificial water oxidation and generally considered to be an outer-sphere oxidant. Herein we report the spectroscopic and crystallographic characterization of 2+ (2)w ith Ce III (NO 3 ) 3 in MeCN.S urprisingly,t he formation of 3 is reversible,t he position of the equilibrium being dependent on the MeCN/water ratio of the solvent. These results suggest that the Fe IV and Ce IV centers have comparable reduction potentials.M oreover,t h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 47 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…Upon addition of 1 equiv CAN, the ferrous precursor 1 is fully oxidized to the ferric state ( Figure S1) and proceeds to generate 2 with additional CAN (see Figure 1 for a spectrum of 2). Just like the related [(L)Fe III (O)Ce IV -(NO 3 ) 4 ] + complexes (L = N4Py or BnTPEN) we previously reported, [10] 2 exhibits an EPR spectrum at 4 K with signals at g = 8.8 and 4.2, characteristic of a rhombic S = 5/2 Fe III center ( Figure S2). Its resonance Raman (rR) spectrum (l exc 515 nm) shows a band at 695 cm À1 (Figure 2 A, Table 1) that is assigned to the Fe-O stretch of the Fe-O-Ce unit, with a frequency flanked by the Fe III -O stretches of corresponding 2(N4Py) (707 cm À1 ) and 2(BnTPEN) (685 cm À1 ) complexes.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Upon addition of 1 equiv CAN, the ferrous precursor 1 is fully oxidized to the ferric state ( Figure S1) and proceeds to generate 2 with additional CAN (see Figure 1 for a spectrum of 2). Just like the related [(L)Fe III (O)Ce IV -(NO 3 ) 4 ] + complexes (L = N4Py or BnTPEN) we previously reported, [10] 2 exhibits an EPR spectrum at 4 K with signals at g = 8.8 and 4.2, characteristic of a rhombic S = 5/2 Fe III center ( Figure S2). Its resonance Raman (rR) spectrum (l exc 515 nm) shows a band at 695 cm À1 (Figure 2 A, Table 1) that is assigned to the Fe-O stretch of the Fe-O-Ce unit, with a frequency flanked by the Fe III -O stretches of corresponding 2(N4Py) (707 cm À1 ) and 2(BnTPEN) (685 cm À1 ) complexes.…”
supporting
confidence: 74%
“…Its resonance Raman (rR) spectrum (l exc 515 nm) shows a band at 695 cm À1 (Figure 2 A, Table 1) that is assigned to the Fe-O stretch of the Fe-O-Ce unit, with a frequency flanked by the Fe III -O stretches of corresponding 2(N4Py) (707 cm À1 ) and 2(BnTPEN) (685 cm À1 ) complexes. [10] The 695 cm À1 band of 2 downshifts to 660 cm À1 upon labeling of the oxo bridge with H 2…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the UV/Vis and EPR experiments,t he substitution reaction of 1-M n+ with CANw as further confirmed by rRaman experiments.F irst, the rRaman spectra of 1-Sc 3+ and 1-Al 3+ (l exc = 405 nm) exhibited isotope-sensitive bands at 790 and 789 cm À1 ,r espectively,w hich shifted to 753 and 752 cm À1 upon 18 Osubstitution (Supporting Information, Figures S8a and S9a);the D16 OÀ 18 O = 37 cm À1 is consistent with the calculated value of 35 cm À1 from Hookesl aw for ad iatomic Mn À Oo scillator.T hus,t he rRaman bands of 1-Sc 3+ and 1-Al 3+ can be assigned for aM n ÀOs tretching vibration of 1-M n+ species.I nterestingly,w hen the rRaman spectra of the reaction solutions of 1-Sc 3+ and 1-Al 3+ with CANwere taken, we found that the bands at 790 and 789 cm À1 completely disappeared (Supporting Information, Figures S8b and S9b). Instead, we observed the appearance of aband at 675 cm À1 for 16 Osamples and aband at 645 cm À1 for 18 Os amples (Supporting Information, Figures S8b and S9b). Since we have shown above that 1-Ce 4+ exhibits an isotopesensitive band at 675 cm À1 (see above), the results of the rRaman experiments demonstrate unambiguously that 1-Ce 4+ was formed in the substitution reactions of 1-Sc 3+ and 1-Al 3+ with CAN( Scheme 1, reaction c).…”
Section: Angewandte Chemiementioning
confidence: 89%
“…[15] More recently,Q ue and co-workers reported the spectroscopic and crystallographic characterization of [(N4Py)Fe III -O-Ce IV (OH 2 )(NO 3 ) 4 ] + (N4Py = N,N-bis(2-pyridylmethyl)-Nbis(2-pyridyl)methylamine), which was obtained from the reaction of [(N4Py)Fe II ] 2+ with 2equiv of CANo r [(N4Py)Fe IV =O] 2+ with Ce III (NO 3 ) 3 . [16] However,b esides the structural information of the Fe-O-Ce species in nonheme iron systems,noother metal-oxo species binding the Ce 4+ ion have been reported yet. Moreover,t ot he best of our knowledge,t he effect of the Ce 4+ ion on the chemical properties of high-valent metal-oxo species has never been discussed previously.H erein, we present the synthesis and structural characterization of ar edox-active Ce IV ion-bound mononuclear nonheme Mn IV =Os pecies,[ (dpaq)Mn IV (O)] + -Ce 4+ (1-Ce 4+ ;d paq = 2-[bis(pyridin-2-ylmethyl)]amino-Nquinolin-8-yl-acetamidate) (Scheme 1).…”
mentioning
confidence: 99%